2017
DOI: 10.4172/0974-8369.1000400
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Leukocyte Counts and Venous Thromboembolism: Results from RETROVE Study

Abstract: Introduction: Different studies have shown a possible increased risk of venous thromboembolism (VTE) and arterial thrombosis in patients with an increased leukocyte count. The underlying mechanisms are not completely understood, but they could partly be explained by the role that white blood cells play in inflammation. Our objective is to investigate investigated the relationship between leukocyte counts and VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…Furthermore, total white blood count was associated with the risk of VTE in medical patients in multivariable analysis, while in surgical patients the association of total WBC and VTE risk was significant at invariable and multivariable analysis. Other studies have reported a high monocyte count to be associated with past VTE 18 . Platelets play a key role in thrombosis 19,20 .…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, total white blood count was associated with the risk of VTE in medical patients in multivariable analysis, while in surgical patients the association of total WBC and VTE risk was significant at invariable and multivariable analysis. Other studies have reported a high monocyte count to be associated with past VTE 18 . Platelets play a key role in thrombosis 19,20 .…”
Section: Resultsmentioning
confidence: 87%
“…Leukocytes contribute significantly to clot formation and are found in both arterial and venous thrombi. 20,21 Leukocytes bind fibrin via integrin receptor α M β 2 (Mac-1), which supports the inflammatory response. 22 Neutrophils, the most abundant leukocyte in circulation, release matrix metalloproteinases, platelet-activating factor, cathepsin G, and elastase.…”
Section: Leukocytesmentioning
confidence: 99%
“…10 With longer follow-up of the Atherosclerosis Risk in Communities (ARIC) study component of LITE and far more events than in our previous analysis, we reexamined the association of hematocrit with VTE incidence. Because a few research studies have associated VTE risk with other aspects of the complete blood count, 8,[11][12][13][14] and diseases manifest as altered levels of these often increase VTE risk, we also tested in a supplemental analysis whether higher leukocyte or platelet counts in ARIC also may be associated with elevated risk of VTE.…”
Section: Introductionmentioning
confidence: 99%